TINJAUAN HUKUM ISLAM DAN HUKUM PERLINDUNGAN KONSUMEN TERHADAP PENJUAL JAMU GENDONG DI KOTA BATUSANGKAR - Melda Anggraini; Hidayati Fitri (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
The law of buying and selling is basically permissible, provided that it is in accordance with the rules that have been established in Islam. The real conditions in the field are still many buying and selling practices that are no longer in accordance with the rules in Islam, whether carried out by sellers or buyers. This study aims to explain and analyze the practice of selling herbal medicine in Batusangkar City in terms of Consumer Protection Law and Islamic Law. This study uses an approach with the type of field research. The subject of this research is the seller of herbal medicine in Baringin village. Data collection techniques used are through observation, interviews, and documentation. Data processing was carried out in a qualitative descriptive manner, then described and classified aspects of certain problems and explained them through effective sentences. The results of the study indicate that in terms of Law Number 8 of 1999 concerning Consumer Protection Law, herbal medicine sellers have not fulfilled consumer rights. Then from Islamic law herbal medicine sellers also have not fulfilled the rights of consumers to get good/hygienic drinks or food according to His word in Surah Al-Baqarah verse 168 concerning consuming halal and good food and drinks, as well as in the hadith of the Prophet Muhammad concerning cleanliness.